Clinical analysis of acute peripheral facial palsy in older adults. Issue 11 (7th November 2022) - Jeong, D Y; Kim, H; Cho, S I
Abstract: Objective: Acute facial palsy is a consequence of various diseases, with the number of patients increasing with advancing age. This study aimed to analyse the clinical characteristics of acute peripheral facial palsy in older adults. Methods: A total of 30 patients with a mean age of 68.4 ± 9.1 years were included in the study. All patients received a standardised investigation and follow up. The hospital charts of the patients with acute facial palsy were reviewed retrospectively. Results: The predominant causes of acute facial palsy in older adults were: Bell's palsy, Ramsay Hunt syndrome, trauma, otitis media and malignancy. At baseline, complete and incomplete facial palsies were seen in 26.7 per cent and 73.3 per cent of patients, respectively. The overall rates of good recovery, partial recovery and no recovery were 66.7 per cent, 10 per cent and 23.3 per cent, respectively. Increased age led to a significantly lower level of recovery in older adults. Conclusion: Bell's palsy and Ramsay Hunt syndrome were the most common aetiologies of acute facial palsy in older adults, and such patients are likely to have incomplete recovery. Active early treatment is necessary for achieving good outcomes in older adults.